Mortality in patients with haematemesis and melaena: a prospective study. Issue 6173 (12th May 1979) - Hunt, P S; Hansky, J; Korman, M G
Abstract : In a prospective study of death in 817 patients with haematemesis and melaena admitted on 894 occasions, the protocol included admission of all patients to a defined unit, early endoscopy and resuscitation, and planned management. Over the three consecutive two-year periods of the study mortality significantly decreased from 9% to 2.4%. Although the operative rate remained the same, the operative mortality fell from 16% to 1.6%. The fall in mortality was greatest in patients with bleeding gastric ulcers. These results suggest that prospective studies with a defined policy can influence the mortality in patients with upper gastrointestinal bleeding.